Representasi Karakter Ayah Pada Film NKCTHI : Nanti Kita Cerita Tentang Hari Ini - Tigy Ambar Silvanari (Universitas Gadjah Mada, 2021)
The background of this research is motivated by an interest in the patriarchal cultural practices that apply to Indonesian society. Where one of them is related to the dominance of men as fathers in the family sphere. A number of roles in the family are constructed in the position of the father. Film is one of the media that can portray father as the main character. The depiction of the father character in Indonesian films in the 90s has shifted from the 2000s to the present. One of the family-themed films that make the main character of the father in the current era is the NKCTHI: Nanti Kita Cerita Tanpa Hari film. This film is interesting to study, because the character of the father is shown by taking pictures from various points of view. So it would be interesting if a study was conducted on the depiction of the father's character in the NKCTHI: Nanti Kita Cerita Tentang Hari Ini film. This study uses a qualitative method with Peirce's semiotic analysis to get a picture of the representation of the father's character through the signs, objects, and interpreters in the scenes in the NKCTHI: Nanti Kita Cerita Tanpa Hari ini film. The results of this study indicate that the character of the father in this film is still represented as a dominant figure through his role as a protector so that it can be associated with the practice of patriarchal culture that is still valid in Indonesia, especially in the family sphere.